2016
DOI: 10.12932/ap0853
|View full text |Cite
|
Sign up to set email alerts
|

Drug allergy evaluation for betalactam hypersensitivity: Cross-reactivity with cephalosporines, carbapenems and negative predictive value

Abstract: Carbapenems and cephalosporines can be safely given to penicillin allergic patients by means of skin testing and if negative, proceeding with a graded challenge. Our calculated NPV for penicillin testing is similar to other studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These individual level barriers originated from lack of confidence in determining the patient’s risk of future reaction, and discomfort managing the consequences to both the patient and healthcare team if adverse reactions developed. This finding is not surprising, as other studies showed that general practitioners were reluctant to prescribe penicillin even after a successful oral challenge [ 26 28 ]. Fragmentation of allergy-related documentation in the EMR and having easy access to second-line antibiotics also reinforced this behavior [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 61%
“…These individual level barriers originated from lack of confidence in determining the patient’s risk of future reaction, and discomfort managing the consequences to both the patient and healthcare team if adverse reactions developed. This finding is not surprising, as other studies showed that general practitioners were reluctant to prescribe penicillin even after a successful oral challenge [ 26 28 ]. Fragmentation of allergy-related documentation in the EMR and having easy access to second-line antibiotics also reinforced this behavior [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 61%
“…Note that this meta-analysis 12 included studies on at least 10 subjects (children and adults) with a documented penicillin allergy (IgE-or T-cell-mediated). In studies carried out since 1990 on more than 25 subjects with proven IgE-mediated allergy to penicillins, [27][28][29][30][31][32][33][34] the rate of positive cephalosporin STs ranged from 0% 28,30 to 33.3% (Table 1). 31 The highest rate was found in the study of ours, 31 in which participants underwent STs with a panel of 9 cephalosporins, including 3 aminocephalosporins (ie, cephalexin, cefadroxil, and cefaclor) that share similar or identical side-chain determinants with the aminopenicillins that were responsible for HSRs in 96% of the 252 patients assessed.…”
Section: Selecting Cephalosporinsmentioning
confidence: 99%
“…31 The highest rate was found in the study of ours, 31 in which participants underwent STs with a panel of 9 cephalosporins, including 3 aminocephalosporins (ie, cephalexin, cefadroxil, and cefaclor) that share similar or identical side-chain determinants with the aminopenicillins that were responsible for HSRs in 96% of the 252 patients assessed. In the aforesaid studies, [27][28][29][30][31][32][33][34] 821 penicillinallergic subjects negative to cephalosporin STs underwent a total of 1825 graded challenges with the related cephalosporins; only 11 challenges (0.6%) were positive. Specifically, there were 7 positive challenges (1.9%) out of 366 performed with aminocephalosporins, and 4 positive challenges (0.3%) out of 1459 carried out with cephalosporins like cefazolin, cefuroxime, ceftriaxone, and ceftazidime that have side chains different from those of penicillins.…”
Section: Selecting Cephalosporinsmentioning
confidence: 99%
“…This high rate of cross-reactivity has decreased since the 1980s. In later reports, approximately 1% of patients who were allergic to penicillin reacted to cephalosporins, likely due to the decrease in the use of first-generation cephalosporins, which have structures similar to that of penicillin [16-19]. In practice, although it has been shown to be incorrect, that overestimation has led to the avoidance of all β-lactam antibiotics if there is a history suggestive of penicillin allergy.…”
Section: Introductionmentioning
confidence: 99%